Beginners and equals: political subjectivity in Arendt and Rancière. Issue 1 (13th April 2012) - Dikeç, Mustafa
Abstract : This article explores the idea of political subjectivity in Hannah Arendt and Jacques Rancière, both of whom I see as thinkers of ruptural and inaugurative politics with a particularly spatial conceptualisation of politics. I start by distinguishing between three strands of thinking about the nature of political subjectification, and I situate Arendt and Rancière's conceptualisations in relation to these. After an examination of their idea of political subjectivity, I offer an interpretation of the movement of sans papiers as it relates to political subjectification. This interpretation also brings out the similarities and differences between Arendt's and Rancière's understanding of politics.